Evaluation of Stratospheric Intrusions and Biomass Burning Plumes on the Vertical Distribution of Tropospheric Ozone Over the Midwestern United States. Issue 18 (14th September 2020) - Wilkins, J. L.; de Foy, B.; Thompson, A. M.; Peterson, D. A.; Hyer, E. J.; Graves, C.; Fishman, J.; Morris, G. A.
Abstract: Naturally occurring ozone‐rich stratosphere‐to‐troposphere transport (STT) intrusions and biomass burning (BB) plumes reaching the surface can contribute to exceedances of the U.S. National Ambient Air Quality Standards for ground‐level ozone (70 ppbv implemented in 2015). Additionally, fires can inject significant pollution into the free troposphere where it can be transported long distances. The combined air quality impacts from these sources on ozone have only been analyzed in a few case studies for the Midwest United States. Here we study ozone impacts in a Midwestern city, for the first time in St. Louis, Missouri, using a series of ozonesonde profiles taken during the Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC 4 RS) field campaign in August–September 2013. All ozonesondes showed enhancements above the background profile levels (~55 ppbv) throughout each tropospheric column. Two models were used to estimate ozone origins in columns. A chemical transport model identified STT enhancements equivalent to 10 to 15 ppbv over the background with a 10% to 15% contribution overall to the column. Two FLEXPART‐WRF simulations, one with smoke in the boundary layer and another with smoke above, identified BB enhancements equivalent to 10 to 80 ppbv. Overall, the total BB contribution is 15% to 30% of the total column. Five ozonesondes showed signatures of mixed BB plumes and STT intrusions. During this study period, BB in the western United States contributed 70% to ozone enhancements in the total column compared to 3% from the central United States and 27% from other areas. Plain Language Summary: Because man‐made emissions are decreasing, concentrations of harmful ozone pollution have also decreased in many areas of the United States. Not all sources can be easily controlled however. For example, biomass burning emits lots of pollutants to the atmosphere, and descending air from the stratosphere can bring with it high levels of ozone. These sources can pollute first the air above us, and then when the air is transported to the surface, it can pollute the air we breathe. In this study we used balloons to measure ozone pollution as it changes from the surface to high in the atmosphere. We then used computer models to identify the sources responsible for higher pollution levels. Our study was part of a major field campaign that took place in the Midwest United States in the summer of 2013. Key Points: Stratospheric intrusions can contribute 10 to 25 ppbv to the background ozone Biomass burning plumes can contribute 10 to 80 ppbv to the background ozone Biomass burning in the western United States can significantly increase Midwest pollution levels